Influence of 2D:4D ratio on fitness parameters and accumulated training load in elite youth soccer players - Nobari, H.; Ruivo Alves, A.; Clemente, F. M.; Pérez-Gómez, J. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background Digit ratio (2D:4D) characterized by the length of the second digit (2D) divided by the length of the fourth digit (4D), is a powerful marker of athletic performance. Some studies showed a negative correlation between 2D:4D ratio and sports performances.